2022
DOI: 10.1001/jamanetworkopen.2022.42676
|View full text |Cite
|
Sign up to set email alerts
|

Statin Use and Survival Among Men Receiving Androgen-Ablative Therapies for Advanced Prostate Cancer

Abstract: ImportanceEpidemiological evidence supports a role for statins in improving survival in advanced prostate cancer, particularly among men receiving androgen-ablative therapies.ObjectiveTo study the association between statin use and survival among men with prostate cancer receiving androgen deprivation therapy (ADT) or androgen receptor axis–targeted therapies (ARATs).Data SourcesThis systemic review and meta-analysis used sources from MEDLINE, EMBASE, Epub Ahead of Print, Cochrane Clinical Trials, Cochrane Sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 57 publications
(395 reference statements)
0
5
0
Order By: Relevance
“…25-27 The combined use of statins with ADT was associated with improved overall survival and reduction in prostate cancer–specific mortality. 28 Interestingly, we observed that a higher proportion of patients in the N2 group (more responders) of the neoadjuvant cohort were already on statin medication at the start of the trials compared with the N1 group (33% v 13%, chi-squared test P = .02). However, we are unable to conclude if statin medication contributed to the lower plasma levels of sphingolipids of the N2 group without controlled conditions (eg, length of treatment time and prestatin plasma levels are unknown).…”
Section: Discussionmentioning
confidence: 73%
“…25-27 The combined use of statins with ADT was associated with improved overall survival and reduction in prostate cancer–specific mortality. 28 Interestingly, we observed that a higher proportion of patients in the N2 group (more responders) of the neoadjuvant cohort were already on statin medication at the start of the trials compared with the N1 group (33% v 13%, chi-squared test P = .02). However, we are unable to conclude if statin medication contributed to the lower plasma levels of sphingolipids of the N2 group without controlled conditions (eg, length of treatment time and prestatin plasma levels are unknown).…”
Section: Discussionmentioning
confidence: 73%
“…In a meta-analysis of 25 cohort studies that included 119,878 patients with PCa, concurrent statin use was associated with improved overall survival by 27% and PCa-specific mortality by 35%. 19 Furthermore, based on promising data from early-stage trials and observational studies, the effect of atorvastatin on PCa progression during ADT treatment is being investigated in an ongoing randomized placebo-controlled phase 3 trial. 20 While high-quality data on the effects of statins on cardiovascular and cancer-related mortality are still needed, the PC360 Working Group felt that the extant effectiveness data and the minimal risks associated with statin use were sufficient to recommend consideration of concurrent moderate-intensity statin initiation in most patients receiving ADT.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have confirmed that statins can reduce the incidence rate of endometrial cancer, ovarian cancer, esophageal cancer, gastric cancer and colorectal cancer [ 16 , 17 ]. In addition, statins can also reduce the mortality of patients with esophageal cancer, gastric cancer, colorectal cancer, prostate cancer and breast cancer [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%